Peer Influences and Its Association with The Risk of Eating Disorders Among Adolescents - Azrimaidaliza Azrimaidaliza; Welly Famelia; Nadia Chalida Nur (Jurnal Kesehatan Masyarakat Andalas, 2022)
The prevalence of eating disorder among adolescents tend to increase worldwide, including in Indonesia. Some factors, such as mass media, peer influences, and body image, were associated with eating disorders. The study aims to determine the association of peer influences with eating disorders among adolescents. This study used a cross-sectional design that utilized a simple random sampling technique among senior high school students in Padang city. Data were collected through self-administration, and online questionnaires were given to 250 participants. The study found that 24.4% of adolescents risk eating disorders. Peer influences associated with eating disorders among adolescents (p-value < 0.05). Adolescents with peer influences had a risk of 2.519 times being eating disorders compared with no peer influences. Mass media, internet access, and body image had no association with eating disorders among adolescents. The current findings suggest that health care professionals should corporate with school institutions on health education to prevent eating disorders among adolescents.